HE CHANGES ON THE TRADITIONAL BELIEFS OF THE BRUNEI MALAY COMMUNITY IN THE NORTH BORNEO (1881- 1963) - DG JUNAIDAH, A. JAMBOL; BEE BASRAH, BEE BASZLEY; NURULASYIKIN, HASSAN; Nur Auni, Ugong; ABDUL RAHMAN, MAD ALI; Mohd Waliuddin, Mohd Razali (Penerbit UMS, 2024)
Religion and traditional beliefs are important aspects of Brunei's Malay community's life. The influence of Islam on this community's traditional beliefs can be seen in almost every aspect of life, from birth to death. The expansion of Islam in North Borneo has altered not only the community's perception of superstitions but also their understanding of the application of true Islamic values in their everyday lives. The arrival of preachers in North Borneo changed the definition of the Bruneian Malay community's understanding and practice at the time. This paper will be discussed from two perspectives: the first is about the forms of practice and traditional beliefs of the Bruneian Malay community, and the second is about the influence of Islam on their traditional beliefs in North Borneo, especially on the west coast. This research will demonstrate that the influence of Islam brought by preachers has successfully changed the perspective and understanding of the Bruneian Malay community towards the guidelines and practices of true Islamic life. It is hoped that this study will be able to meet the objective of showing that, apart from political, economic, and social factors, aspects of religion and traditional beliefs also played a significant role in shaping the mentality and life pattern of the Bruneian Malay community after Sabah achieved independence.